Perioperative blood transfusion does not affect recurrence-free and overall survivals after curative resection for intrahepatic cholangiocarcinoma: a propensity score matching analysis - Zhou, Pei-Yun; Tang, Zheng; Liu, Wei-Ren; Tian, Meng-Xin; Jin, Lei; Jiang, Xi-Fei; Wang, Han; Tao, Chen-Yang; Ding, Zhen-Bin; Peng, Yuan-Fei; Qiu, Shuang-Jian; Dai, Zhi; et al. (BMC cancer, 2017)
Whether perioperative blood transfusions (PBTs) adversely influence oncological outcomes for intrahepatic cholangiocarcinoma (ICC) patients after curative resection remains undetermined. Of the 605 patients who underwent curative liver resection for ICC between 2000 and 2012, 93 received PBT. We conducted Cox regression and variable selection logistic regression analyses to identify confounding factors of PBT. Propensity score matching (PSM) and Cox regression analyses were used to compare the overall survival (OS) and disease-free survival (DFS) between the patients with or without PBT. After exclusion, 93 eligible patients (15.4%) received PBT, compared with 512 (84.6%) who did not receive PBT; the groups were highly biased in terms of the propensity score (PS) analysis (0.096 ± 0.104 vs. 0.479 ± 0.372, p < 0.001). PBT was associated with an increased risk of OS (HR: 1.889, 95% CI: 1.446-2.468, p < 0.001) and DFS (HR: 1.589, 95% CI: 1.221-2.067, p < 0.001) in the entire cohort. After propensity score matching (PSM), no bias was observed between the groups (PS,0.136 ± 0.117 VS. 0.193 ± 0.167, p = 0.785). In the multivariate Cox analysis, PBT was not associated with increased risks of OS (HR: 1.172, 95% CI: 0.756-1.816, p = 0.479) and DFS (HR: 0.944, 95% CI: 0.608-1.466, p = 0.799). After propensity score adjustment, PBT was still not associated with OS or DFS after ICC curative resection. The present study found that PBT did not affect DFS and OS after curative resection of ICC.